2018
DOI: 10.1371/journal.pone.0197214
|View full text |Cite
|
Sign up to set email alerts
|

5000 years of dietary variations of prehistoric farmers in the Great Hungarian Plain

Abstract: The development of farming was a catalyst for the evolution of the human diet from the varied subsistence practices of hunter-gatherers to the more globalised food economy we depend upon today. Although there has been considerable research into the dietary changes associated with the initial spread of farming, less attention has been given to how dietary choices continued to develop during subsequent millennia. A paleogenomic time transect for 5 millennia of human occupation in the Great Hungarian Plain spanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
30
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 53 publications
9
30
1
1
Order By: Relevance
“…The δ 13 C values of the burials from Mözs were higher than those from previously investigated Early Neolithic to Early Bronze Age sites (c. 6500-1400 BC) in the Carpathian Basin [97,98]. This result attests to remarkable contributions of millet to the human diet, a C 4 plant, which first started to play a role in the every-day diet in the area during the Late Bronze Age and Early Iron Age [97,98]. Ancient agrarian texts, archaeobotanical evidence, and stable isotope data state that millet was also cultivated during the Roman period.…”
Section: Implications Of the Dietary Habitscontrasting
confidence: 65%
“…The δ 13 C values of the burials from Mözs were higher than those from previously investigated Early Neolithic to Early Bronze Age sites (c. 6500-1400 BC) in the Carpathian Basin [97,98]. This result attests to remarkable contributions of millet to the human diet, a C 4 plant, which first started to play a role in the every-day diet in the area during the Late Bronze Age and Early Iron Age [97,98]. Ancient agrarian texts, archaeobotanical evidence, and stable isotope data state that millet was also cultivated during the Roman period.…”
Section: Implications Of the Dietary Habitscontrasting
confidence: 65%
“…In both cases, this is the time of the Tumulus culture, characterized by intensive cross-regional (east–west) connectivity and marked socio-economic change 84 [125], 85 , 86 . Here the human stable isotope studies showed a significant increase in δ 13 C values, relative to the previous periods, in the second half of the 2nd millennium bc 87 . Early and Middle Bronze Age archaeobotanical assemblages from the wider region include rare finds of millet 88 , but these have not been dated.…”
Section: Discussionmentioning
confidence: 63%
“…The increased socio-political and economic connectivity across the Mediterranean in the second half of the 2nd millennium bc 81,82,84,96,98 perhaps facilitated a 'southerly' route of transfer of millet into peninsular Italy and the Balkans, with the city of Mycenae as the potential "power node" 94 [87]. However, the majority of Late Bronze Age (1600-1100 bc) archaeobotanical finds of broomcorn millet in Greece are located in the north, including several large deposits 40 , of which the one at Assiros was direct-dated to the fourteenth century cal bc (1405-1305 cal bc [95.4% confidence], refined to 1374-1339 cal bc [95.4% probability] according to the published site chronological model) 99 .…”
Section: Discussionmentioning
confidence: 99%
“…Following the criteria by Buikstra and Ubelaker (1994), we divided the specimens into three age categories: young adults (20-35 years), middle adults (35-50 years), old adults (50+). Sex diagnosis was based on skull and pelvis morphology (Acsádi and Nemeskéri 1970) and osteometric characters of the skull (Giles and Elliot 1963;Demoulin 1972), mandible (Piquet 1956), scapula (Olivier and Pineau 1958), humerus (Ferembach et al 1977(Ferembach et al -1979(Ferembach et al , 1980Dittrick and Suchey 1986;France and Horn 1988), ulna (France 1998), femur (Iordanidis 1961;Dittrick and Suchey 1986), tibia (Ferembach et al 1977(Ferembach et al -1979(Ferembach et al , 1980 and talus (Gualdi-Russo 2007).…”
Section: Samplesmentioning
confidence: 99%